Agriculture and Groundwater Feeding Billions from the Ground Up - Döll, Petra; Villholth, Karen G.; Gruère, Guillaume P.; Wang, Jinxia; Ringler, Claudia (2017)
Presentations from the Global Forum for Food and Agriculture: Agriculture and water - Key to feeding the world, January 20, 2017, Berlin, Germany.